Study on Bainitic Transformation by Dilatometer and In Situ LSCM - Long, Xiaoyan (Materials (Basel), 2019)
This study investigates the bainitic transformation kinetics of carbide-free bainitic steel with Si + Al and carbide-bearing bainitic steel without Si + Al, as well as the phase transformation and microstructure through in situ high-temperature laser scanning confocal microscopy. Results show that bainitic ferrite plates preferentially nucleate at the grain boundary. New plates nucleate on previously formed ones, including two dimensions which appear on a plane where a three-dimensional space of bainitic ferrite forms. Nucleation on the formed bainitic ferrite is faster than that at the grain boundary in some grains. The bainitic ferrite growth at the austenite grain boundary is longer and has a faster transformation rate. The bainitic ferrite growth on the formed bainitic ferrite plate is shorter and has a slower transformation rate. The location and number of nucleation sites influence the thickness of the bainitic ferrite. The higher the number of plates preferentially nucleating at the original austenite grain boundary, the greater the thickness of the bainitic ferrite.